PENGARUH JENIS DAN KONSENTRASI HIDROKOLOID TERHADAP SIFAT FISIK DAN ORGANOLEPTIK VELVA APEL MANALAGI - Handoko, Ivan C.; Matoetina, Maria; Widyawati, Paini Sri (Jurnal Teknologi Pangan dan Gizi, 2017)
Manalagi apple is one of local commodity. Processing apples into velva is one effort to food iversification and extend the shelf life of apples. Velva is a frozen dessert product made from crushed fruit (puree) and it doesn’t use milk fat. In general, body and texture of velva are influenced by the stability colloidal system which is influenced by the ratio of puree, water, and sugar. This research was done by Factorials Random Design using Hydrocolloid Type Factor (pectin (H1), gelatin (H2), and Na-CMC (H3)) and Hydrocolloid Concentration Factor (0,3% (K1) and 0,5% (K2) w/w) with four times replications. The parameters are consist of Physical Properties (viscocity, overrun (%), and melting rate) and Organoleptic Properties (color, spoonable, sandness, melting in the mouth, and flavor). Data will be analyzed using ANOVA at α= 5%, then continued by DMRT at α= 5% for the properties that gave the significant effect. Based on the result of ANOVA at α = 5% was known that Hydrocolloid type gave influenced to the viscosity (before and during aging). Hydrocolloid concentration gave influenced to the viscosity before aging. The interaction between hydrocolloid type and concentration gave influenced to overrun and organoleptic properties (spoonable, sandness, and color). Viscosity during aging had a range from 1024-4311%, overrun 5,19-18,07%. The preference test for spoonable was 5,0500-6,2000, sandness was 4,9875-6,2500, melting in the mouth was 5,6625-6,1875, flavor was 5,6625-6,2375, and color was 3,3375-6,2125.